A Red Fluorescent Protein-Based Probe for Detection of Intracellular Reactive Sulfane Sulfur - Zimai Li; Qingda Wang; Yongzhen Xia; Luying Xun; Huaiwei Liu (MDPI AG, 2020)
Reactive sulfane sulfur, including persulfide and polysulfide, is a type of regular cellular component, playing an antioxidant role. Its function may be organelle-dependent; however, the shortage of probes for detecting organellar reactive sulfane sulfur has hindered further investigation. Herein, we reported a red fluorescent protein (mCherry)-based probe for specifically detecting intracellular reactive sulfane sulfur. By mutating two amino acid residues of mCherry (A150 and S151) to cysteine residues, we constructed a mCherry mutant, which reacted with reactive sulfane sulfur to form an intramolecular -Sn- bond (n ≥ 3). The bond largely decreased the intensity of 610 nm emission (excitation at 587 nm) and slightly increased the intensity of 466 nm emission (excitation at 406 nm). The 466/610 nm emission ratio was used to indicate the relative abundance of reactive sulfane sulfur. We then expressed this mutant in the cytoplasm and mitochondria of Saccharomyces cerevisiae. The 466/610 nm emission ratio revealed that mitochondria had a higher level of reactive sulfane sulfur than cytoplasm. Thus, the mCherry mutant can be used as a specific probe for detecting reactive sulfane sulfur in vivo.